2010
DOI: 10.1525/si.2010.33.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Running the Gauntlet: Women's Use of Emotion Management Techniques in the Abortion Experience

Abstract: Women who have abortions are caught in the crossfire of a heated ideological battle. The prochoice contention is that most women feel relieved after terminating an unwanted pregnancy. The antiabortion camp asserts killing an unborn child psychologically scars the mother. Drawing on in-depth interviews with forty women who have terminated a pregnancy, this study examines how the clashing emotion culture of abortion politics shapes women's feelings about abortion. Findings indicate that women use behavioral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…Experiencing complex emotions and having strong feelings after an abortion—even negative ones—does not indicate that a woman feels she made the wrong decision. Our results are consistent with prior research that suggests that postabortion emotions vary from woman to woman—and, for a given woman, from abortion to abortion—largely as a function of life circumstances, difficulty with decision making and social support, including from romantic partners . Mechanisms targeting all women, such as regulations or information requirements, do not address these issues and may, in fact, exacerbate negative emotions.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Experiencing complex emotions and having strong feelings after an abortion—even negative ones—does not indicate that a woman feels she made the wrong decision. Our results are consistent with prior research that suggests that postabortion emotions vary from woman to woman—and, for a given woman, from abortion to abortion—largely as a function of life circumstances, difficulty with decision making and social support, including from romantic partners . Mechanisms targeting all women, such as regulations or information requirements, do not address these issues and may, in fact, exacerbate negative emotions.…”
Section: Resultssupporting
confidence: 81%
“…Consistent with prior studies, we found that the main variables associated with experiencing primarily negative emotions were aspects of the pregnancy decision-making process and social environment. 14,16,31,33,34 Specifi cally, women' s likelihood of reporting primarily negative emotions was positively associated with the degree to which they had planned a pregnancy and had had diffi culty deciding to seek abortion. The abortion decision is infl uenced by many factors, including desired family structure, cultural or spiritual beliefs, personal decision-making style, physical health and partner or social support.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…Matha Copp, in her () study of an employment program for workers with developmental disabilities, termed these efforts to manage emotions before they arise “preventive emotion work.” The supervisors in Copp's fieldsite worked to construct a collectively jovial mood during their shifts in order to keep workers from slipping into more problematic affective states, and looked closely for any sign that a worker might be in a bad mood so that they could intervene and work to push them in a cheerful emotional direction before more overt problems arose. In another instance of preventive emotion work, Jennifer Keys () found that women facing an unwanted pregnancy often “strategically dodged or deliberately approached” emotionally charged symbols (for instance, an ultrasound image) or people who might help them feel the way they wanted to feel about the pregnancy, and avoid feelings that would make decision‐making more difficult.…”
Section: Cultivating Hope and Protecting Fragile Emotional Statesmentioning
confidence: 99%